Web-based MINDfulness and Skills-based distress reduction in cancer (MINDS): study protocol for a multicentre observational healthcare study. Issue 8 (13th August 2020) - Bäuerle, Alexander; Teufel, Martin; Schug, Caterina; Skoda, Eva-Maria; Beckmann, Mingo; Schäffeler, Norbert; Junne, Florian; Erim, Yesim; Zipfel, Stephan; Graf, Johanna
Abstract : Introduction: Although a high percentage of patients with cancer experience severe psychological distress, few of them receive psycho-oncological care, largely due to barriers on the side of patients and healthcare providers that pose great challenges to delivering such care. In response, low-threshold, self-guided eHealth interventions can enable patients with cancer to deal independently and effectively with disease-related challenges and distress. Mindfulness and Skills-Based Distress Reduction in Oncology Training, nicknamed Make It Training, is one such innovative, self-guided eHealth intervention. In our study, we propose to assess different characteristics of such patients in order to define target populations for Make It Training, evaluate the intervention in terms of its usability, feasibility and sustainability and gather longitudinal data concerning the intervention's efficacy. Methods and analysis: Self-guided and web-based Make It Training consists of eight 30 min modules involving the use of techniques of mindfulness therapy, cognitive–behavioural therapy and acceptance and commitment therapy to be completed in a 4-month period. In our observational study, adult patients with cancer who possess adequate German language skills and provide their informed consent will be recruited at Essen, Erlangen and Tübingen University Hospitals at outpatient oncological institutions and via online channels. Patients will undergo a baseline online assessment (T0), an assessment directly after completing the intervention (T1) and assessments 3 and 6 months later (T2 and T3, respectively). With the results of those assessments, we will perform descriptive analyses of their sociodemographic and medical data, compare means and conduct regression analyses. Ethics and dissemination: The Ethics Committees of the University Hospitals Essen, Erlangen and Tübingen have approved the study (19-8643-BO, 27_19 B, 293/2018BO1). Results will be published in peer-reviewed journals and conference presentations. Trial registration number: DRKS00017119.